The relationships among coaches` and athletes` perceptions of coaching staff cohesion, team cohesion, and performance - Zakrajsek, R. A.; Abildso, C. G.; Hurst, J. R.; Watson II, J. C. (Athletic Insight - The Online Journal of Sport Psychology, 2007)
This study explored coaches` and athletes` perceptions of coaching staff cohesion (CSC) and their relationships with team cohesion and performance. Eighteen NCAA Division I, II, and III teams participated. Coaches completed the Coaching Staff Cohesion Scale (CSCS; Martin, 2002). Athletes completed a modified CSCS, the Group Environment Questionnaire (GEQ; Carron, 1985), and an item of perceived team performance. Significant differences were found between athletes` and coaches` perceptions of CSC (t = 7.162, p < .001). Athletes` perception of CSC was significantly correlated with three GEQ subscales: Individual Attraction to Group-Task (r = .610, p < .01), Group Integration-Task (r = .498, p < .05), and Group Integration-Social (r = .492, p < .05). Coaches` perceptions of CSC were significantly correlated with Individual Attraction to Group-Task (r = .553, p < .05). A significant relationship was also found with task cohesion (Individual Attraction to Group-Task, r = .612, p < .01 and Group Integration-Task, r = .739, p < .001) and performance.